What is heterodox economics? - Wrenn, Mary V., author; Stanfield, Ron, advisor; Swanson, Lou, committee member; Marangos, John, committee member; Phillips, Ronnie, committee member (Colorado State University. Libraries, 2004)
The nature of heterodox economics currently eludes description. Preliminary research suggests that heterodox economics is not coherently defined and that those individuals who identify their work as such appear to do so in isolated groups with little interchange. What is necessary in order to understand the iconoclastic opposition of the heterodoxy and ultimately, their purpose, is an articulation in the differences between them as well as their research program, in addition to those features of the heterodoxy remain underdeveloped. The purpose of this study is to uncover this dissent and provide clarification of the heterodoxy through an examination consisting of three parts: a tertiary review of history of economics texts, a secondary literature review of contemporary discourse, and a survey of historians of economic thought. Given the historical groping in economics for meaning, purpose, and method, confusion in identity is understandable but not inevitable. It is hoped that this study will provide some degree of clarification and articulation in this regard.